Rootone-F Concentration and Growing Media for Increasing the Growth of Jasmine Cuttings from Banjar Regency, South Kalimantan Province - Hilda Susanti; Indya Dewi; Ronaldo Harianto (Institut Pertanian Bogor, 2025)
Jasmine is a superior floriculture commodity in the Banjar Regency with high economic potential. Local jasmine farmers do not yet have operational standards for jasmine propagation. This study aimed to study various concentrations of Rootone-F with growing media to increase the growth of jasmine cuttings from the Banjar Regency. The experiment used a completely randomized factorial design. The first factor was the concentration of Rootone (a0 = 0, a1 = 100 ppm, a2 = 200 ppm, a3 = 300 ppm, a4 = 400 ppm) and and the second factor is the growing medium (m1 = soil + chicken manure (1:1), m2 = soil + chicken manure + sand (1:1:1), m3 = soil + chicken manure + rice husk (1:1:1), and m4 = soil + chicken manure + burnt rice husk (1:1:1). The results showed that the interaction between Rootone concentration treatment and growing media significantly affected the number of leaves at 8 WAP. Single treatment with Rootone had a significant effect on budding time. Single treatment with growing media had a very significant effect on the time of budding and the percentage of cutting growth. The recommendation obtained from the results of this study is that the provision of 400 ppm Rootone and a growing medium of soil + chicken manure + burnt rice husks can be used to increase the growth of jasmine cuttings. The results obtained from this study can be used to develop a protocol to produce high-quality jasmine planting material through cuttings. Keywords: chicken manure, rice husk, Rootone-F